2006
DOI: 10.1021/jp062454+
|View full text |Cite
|
Sign up to set email alerts
|

15N MAS NMR Studies of Cph1 Phytochrome:  Chromophore Dynamics and Intramolecular Signal Transduction

Abstract: Solid-state nuclear magnetic resonance (NMR) is applied for the first time to the photoreceptor phytochrome. The two stable states, Pr and Pfr, of the 59-kDa N-terminal module of the cyanobacterial phytochrome Cph1 from Synechocystis sp. PCC 6803 containing a uniformly 15N-labeled phycocyanobilin cofactor are explored by 15N cross-polarization (CP) magic-angle spinning (MAS) NMR. As recently shown by 15N solution-state NMR using chemical shifts [Strauss, H. M.; Hughes, J.; Schmieder, P. Biochemistry 2005, 44, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
67
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 49 publications
5
67
0
Order By: Relevance
“…Early NMR spectroscopic studies on proteolytic phytochrome fragments (12,13) indicated that this isomerization occurs at the C15═C16 double bond (for numbering, see Fig. 1A), a geometrical change in line with vibrational spectroscopic investigations (14)(15)(16) and results from recent 13 C solid-state NMR (17,18) in which the most significant changes during the light-triggered conversions are confined to rings C and D. Exact geometries of the chromophore in the Pr state have been resolved as periplanar ZZZssa configurations in bacteriophytochromes from Deinococcus radiodurans (19) and Rhodopseudomonas palustris (20) as well as in the more plant-phytochrome-like Cph1 from the cyanobacterium Synechocystis 6803 (21). On the other hand, the crystal structure of the unusual bacteriophytochrome PaBphP Pseudomonas aeruginosa (22) whose ground state is Pfr shows a ZZEssa conformation, consistent with the expected primary photochemistry at the C15═C16 double bond (Fig.…”
supporting
confidence: 70%
“…Early NMR spectroscopic studies on proteolytic phytochrome fragments (12,13) indicated that this isomerization occurs at the C15═C16 double bond (for numbering, see Fig. 1A), a geometrical change in line with vibrational spectroscopic investigations (14)(15)(16) and results from recent 13 C solid-state NMR (17,18) in which the most significant changes during the light-triggered conversions are confined to rings C and D. Exact geometries of the chromophore in the Pr state have been resolved as periplanar ZZZssa configurations in bacteriophytochromes from Deinococcus radiodurans (19) and Rhodopseudomonas palustris (20) as well as in the more plant-phytochrome-like Cph1 from the cyanobacterium Synechocystis 6803 (21). On the other hand, the crystal structure of the unusual bacteriophytochrome PaBphP Pseudomonas aeruginosa (22) whose ground state is Pfr shows a ZZEssa conformation, consistent with the expected primary photochemistry at the C15═C16 double bond (Fig.…”
supporting
confidence: 70%
“…That these peaks were below 180 ppm was consistent with all of these nitrogens being protonated at neutral pH (65,66). Interestingly, for Syn-Cph1(PAS-GAF-PHY) two of these peaks overlapped, indicative of similar chemical environments (32,33), whereas in SyB-Cph1(GAF) they were more uniformly resolved, indicative of more distinct chemical environments (Fig. 8B).…”
Section: Syn-cph1supporting
confidence: 54%
“…If we assume that the B-and C-rings are in similar chemical environments and are more rigidly held via their propionate side chains (10,19), then the moving pyrrole ring is best assigned to the A-ring. In support, Rohmer et al (33) tentatively assigned a similar 15 N chemical shift, which moved from 146.8 to 142.8 ppm during photoconversion, to the A-ring nitrogen of Synechocystis Cph1(PAS-GAF-PHY) fragment.…”
Section: Novel Features Of Sya-cph1 and Syb-cph1 Enable Structuralmentioning
confidence: 91%
See 2 more Smart Citations